2016
DOI: 10.1038/nmat4766
|View full text |Cite
|
Sign up to set email alerts
|

Conductive MOF electrodes for stable supercapacitors with high areal capacitance

Abstract: Owing to their high power density and superior cyclability relative to batteries, electrochemical double layer capacitors (EDLCs) have emerged as an important electrical energy storage technology that will play a critical role in the large-scale deployment of intermittent renewable energy sources, smart power grids, and electrical vehicles. Because the capacitance and charge-discharge rates of EDLCs scale with surface area and electrical conductivity, respectively, porous carbons such as activated carbon, carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
1,236
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,029 publications
(1,320 citation statements)
references
References 30 publications
23
1,236
2
5
Order By: Relevance
“…The surface area and porosity of MOFs far exceed those of activated carbon (AC), potentially challenging the leading role of carbon electrodes in EDLCs [36], whereas MOFs conventionally coupled with exhibiting an extremely low electrical conductivity, which has thus far prevented the use of MOFs as electrode materials in EDLCs. Very recently, Dincǎ et al [37] showed that porous MOF Ni 3 (HITP) 2 has a high electrical conductivity and is a promising electrode material for use in EDLCs; a large capacitance of~18 μF cm −2 was achieved without the use of any conductive additives or other binders, which is greater than the capacitance achieved using most carbon-based electrodes. Based on SCIENCE CHINA Materials.…”
Section: Novel Kinds Of Materialsmentioning
confidence: 99%
“…The surface area and porosity of MOFs far exceed those of activated carbon (AC), potentially challenging the leading role of carbon electrodes in EDLCs [36], whereas MOFs conventionally coupled with exhibiting an extremely low electrical conductivity, which has thus far prevented the use of MOFs as electrode materials in EDLCs. Very recently, Dincǎ et al [37] showed that porous MOF Ni 3 (HITP) 2 has a high electrical conductivity and is a promising electrode material for use in EDLCs; a large capacitance of~18 μF cm −2 was achieved without the use of any conductive additives or other binders, which is greater than the capacitance achieved using most carbon-based electrodes. Based on SCIENCE CHINA Materials.…”
Section: Novel Kinds Of Materialsmentioning
confidence: 99%
“…At the end of this portion, what we want to introduce is the application of metal oxide frameworks (MOFs). [38] As known, MOFs, a class of highly porous materials, have attracted researchers' attention a lot since 1990s. [39] Facing two intrinsic problems of MOFs (insufficient mechanical/ chemical stability and low electrochemical conductivity), we took measures to enhance the pseudocapacitiance of MOFs by doping metal oxides into the system with one-step precipitation.…”
Section: Electrode Nanomaterials Of Electrochemical Energy Storage Devicementioning
confidence: 99%
“…Hence, the exploitation of energy storage devices to efficiently store renewable energy is critical [4]. Among the various energy storage systems (EESs), supercapacitors (SCs) have been regarded as one of the most promising emerging energy storage device because of their significantly long cycling life and high power density [5][6][7]. However, their practical applications have been seriously restricted by the relatively low energy density of SCs, which is mainly related to the structures and properties of active materials.…”
Section: Introductionmentioning
confidence: 99%
“…In general, carbon materials are commonly used in EDLCs as electrode materials. Conventional EDLCs store the charge by ion adsorption at high-surface-area porous carbon electrodes [7,8]. But the amorphous structure and rich microporous structure of carbon electrodes can lead to low electrical conductivity and high charge transfer resistance, resulting in significantly capacitive performance decay at high current density [9].…”
Section: Introductionmentioning
confidence: 99%